BRIDGING THE GAP: HOW MANAGEMENT ACCOUNTING PRACTICES MEDIATE THE EFFECT OF IT TOOLS ON ENTERPRISE PERFORMANCE – EVIDENCE FROM MSMEs (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Micro, small, and medium enterprises (MSMEs) are increasingly encouraged to adopt information technology (IT) tools to remain competitive. Yet, the mechanism through which such technology translates into superior enterprise performance remains insufficiently understood. Drawing on contingency theory, this study examines whether management accounting practices—operationalised through budget practice—mediate the relationship between IT tools and enterprise performance among MSMEs. Data were collected through a survey of MSME owners/managers and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The measurement model demonstrates adequate convergent and discriminant validity. In contrast, the structural model indicates that IT tools exert a strong positive influence on budget practice, and that budget practice, in turn, positively influences enterprise performance. However, the direct path from IT tools to enterprise performance is not statistically significant. In contrast, the indirect path through budget practice is significant, indicating that budget practice fully mediates the effect of IT tools on enterprise performance. These findings suggest that the performance benefits of IT investment in MSMEs are not automatic but are realised through improved internal management accounting practices. The study contributes to the management accounting literature by clarifying the mediating mechanism linking technology adoption and performance in a resource-constrained MSME setting and by offering practical implications for MSME actors and policymakers seeking to maximise returns on IT investment.